Kinetics and Mechanism of Mineral Respiration: How Iron Hemes Synchronize Electron Transfer Rates. Issue 30 (28th January 2020) - Chabert, Valentin; Babel, Lucille; Füeg, Michael P.; Karamash, Maksym; Madivoli, Edwin S.; Herault, Nelly; Dantas, Joana M.; Salgueiro, Carlos A.; Giese, Bernd; Fromm, Katharina M.
Abstract: Anaerobic microorganisms of the Geobacter genus are effective electron sources for the synthesis of nanoparticles, for bioremediation of polluted water, and for the production of electricity in fuel cells. In multistep reactions, electrons are transferred via iron/heme cofactors of c‐type cytochromes from the inner cell membrane to extracellular metal ions, which are bound to outer membrane cytochromes. We measured electron production and electron flux rates to 5×10 5  e s −1 per G. sulfurreducens. Remarkably, these rates are independent of the oxidants, and follow zero order kinetics. It turned out that the microorganisms regulate electron flux rates by increasing their Fe 2+ /Fe 3+ ratios in the multiheme cytochromes whenever the activity of the extracellular metal oxidants is diminished. By this mechanism the respiration remains constant even when oxidizing conditions are changing. This homeostasis is a vital condition for living systems, and makes G. sulfurreducens a versatile electron source. Abstract : The bacterium Geobacter sulfurreducens requires extracellular metal salts for respiration. Each microorganism produces 5×10 5 electrons per second, which reduce the metal ions bound to the outer membrane cytochromes. With iron heme cofactors of c ‐type cytochromes, the electron flow is independent of the concentration and type of oxidant. This results in ATP homeostasis.